2013
DOI: 10.1103/physreva.87.013429
|View full text |Cite
|
Sign up to set email alerts
|

Maximum attainable field-free molecular orientation of a thermal ensemble with near–single-cycle THz pulses

Abstract: Recently, single-cycle THz pulses have been demonstrated in the laboratory to successfully induce field-free orientation in gas-phase polar molecules at room temperature [Phys. Rev. Lett. 107, 163603 (2011)]. In this paper, we examine the maximum attainable field-free molecular orientation with optimally shaped linearly polarized near-single-cycle THz laser pulses of a thermal ensemble. Large-scale benchmark optimal control simulations are performed, including rotational energy levels with the rotational quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The rotation of small molecules has been studied from the viewpoint of non-adiabatic molecular alignment [1][2][3] or molecular orientation [4][5][6][7][8][9][10]. Non-adiabatic molecular alignment has been experimentally realized using non-resonant broadband optical pulses [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The rotation of small molecules has been studied from the viewpoint of non-adiabatic molecular alignment [1][2][3] or molecular orientation [4][5][6][7][8][9][10]. Non-adiabatic molecular alignment has been experimentally realized using non-resonant broadband optical pulses [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulation by Liao et al [24] showed that quite high degrees of orientation of OCS molecules at 100 K are achieved by applying strong near-single-cycle THz pulses with a maximum amplitude of several GV/m. Although such strong THz pulses are available at accelerator facilities, the techniques for generating them mainly use optical rectification [26,27].…”
Section: Introductionmentioning
confidence: 98%
“…An alternate approach is to use (resonant) permanent dipole interaction [21][22][23][24][25]. The numerical simulation by Liao et al [24] showed that quite high degrees of orientation of OCS molecules at 100 K are achieved by applying strong near-single-cycle THz pulses with a maximum amplitude of several GV/m.…”
Section: Introductionmentioning
confidence: 99%
“…In view of experimental applications in quantum control, it is also desirable to design pulse sequences with a zero global time-integrated area. Several works have pointed out the inherent experimental difficulties associated with the use of non-zero area fields [21][22][23][24][25], in particular for laser fields in the THz regime. Since the dc component of the field is not a solution of Maxwell's equation, such pulses are distorted when they propagate in free space as well as through focusing optics.…”
Section: Introductionmentioning
confidence: 99%